EPCT-07. ID1 IS A KEY TRANSCRIPTIONAL REGULATOR OF DIPG INVASION AND IS TARGETABLE WITH CANNABIDIOL. (1st June 2021) - Nand Yadav, Viveka; Harris, Micah K; Thomas, Chase; Stallard, Stefanie; Woo, Rinette; Siddaway, Robert; Qin, Tingting; Cummings, Jessica R; Mullan, Brendan; Siada, Ruby; Ravindran, Ramya; Niculcea, Michael; et al.
Abstract: Diffuse intrinsic pontine gliomas (DIPGs) are lethal pediatric brain tumors with no effective therapies beyond radiation. The highly invasive nature of DIPG is key to its aggressive phenotype, but the factors and mechanisms contributing to this aggressive invasion are unknown. Inhibitor of DNA binding (ID) proteins, key regulators of lineage commitment during embryogenesis, are implicated in tumorigenesis in multiple human solid tumors. Prior work showed that recurrent H3F3A and ACVR1 mutations increase ID1 expression in cultured astrocytes. However, the impact and targetability of ID1 have not been explored in human DIPG. Exome and transcriptome sequencing analyses of multi-focal DIPG tumors and normal brain tissue from autopsy (n=52) revealed that ID1 expression is significantly elevated in DIPG samples. Higher ID1 expression correlates with reduced survival in DIPG patients and increased regional invasion in multi-focal autopsy samples. Analyses of developing mouse brain RNA/ChIP-Seq data revealed high ID1 expression and H3K27ac promoter binding in prenatal hindbrain compared to all other prenatal and postnatal brain regions. ChIP-qPCR for H3K27ac and H3K27me3 revealed that ID1 gene regulatory regions are epigenetically poised for upregulation in DIPG tissues compared to normal brain, regardless of H3/ACVR1 mutational status. These data support that the developing pons is regionally poised for ID1 activation. Genetic (shRNA) ID1 knockdown of primary human H3.3K27M-DIPG cells (DIPG007) resulted in significantly reduced invasion/migration and significantly improved survival of K27M-DIPG mice. Knockdown of ID1 in DIPG cells also resulted in down-regulation of the WNK1-NKCC1 pathway, which regulates tumor cell electrolyte homeostasis and migration. Finally, treatment of DIPG007 cells with cannabidiol (CBD) reduced ID1 levels, viability of DIPG cells and significantly improved survival of K27M-DIPG mice. In summary, our findings indicate that multifactorial (genetic and regional) epigenetic upregulation of ID1 drives DIPG invasiveness; and that targeting ID1 with CBD could potentially be an effective therapy for DIPG.